2021
DOI: 10.1002/advs.202101957
|View full text |Cite|
|
Sign up to set email alerts
|

DDIT4 S‐Nitrosylation Aids p38‐MAPK Signaling Complex Assembly to Promote Hepatic Reactive Oxygen Species Production

Abstract: Mitogen-activated protein kinase (MAPK) signaling plays a significant role in reactive oxygen species (ROS) production. The authors have previously shown that Brahma-related gene 1 (BRG1), a chromatin remodeling protein, contributes to hepatic ROS accumulation in multiple animal and cellular models of liver injury. Here it is reported that DNA damage-induced transcript 4 (DDIT4) is identified as a direct transcriptional target for BRG1. DDIT4 overexpression overcomes BRG1 deficiency to restore ROS production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“… 47 In addition to cardiac diseases, relevant studies in other diseases have shown that DDIT4 mediates the apoptotic process, for example, Lynn M Knowles et al verified that increasing DDIT4 induces caspase-8 mediated tumor cell apoptosis via negatively regulating the mTOR signaling pathway. 48 And Li revealed that DDIT4 can promote the production of ROS in liver injury, 49 which suggests that the expression of DDIT4 is related to the injury of cells. The detailed functional mechanisms of DDIT4 in DCM remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 47 In addition to cardiac diseases, relevant studies in other diseases have shown that DDIT4 mediates the apoptotic process, for example, Lynn M Knowles et al verified that increasing DDIT4 induces caspase-8 mediated tumor cell apoptosis via negatively regulating the mTOR signaling pathway. 48 And Li revealed that DDIT4 can promote the production of ROS in liver injury, 49 which suggests that the expression of DDIT4 is related to the injury of cells. The detailed functional mechanisms of DDIT4 in DCM remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…All the animal experiments were reviewed and approved by the Nanjing Medical University Ethics Committee on Humane Treatment of Laboratory Animals. To induce liver fibrosis, male C57BL/6 mice were injected with CCl 4 (1.0 mL/kg as 50% vol/vol) or subjected to bile duct ligation (BDL) as previously described ( Wang Q. et al, 2020 ; Li et al, 2021 ). Picrosirius red staining was performed with paraffin-embedded liver sections using a commercially available kit (Sigma Aldrich) as previously described ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To induce liver fibrosis, male C57BL/6 mice were injected with CCl 4 (1.0 mL/kg as 50% vol/vol) or subjected to bile duct ligation (BDL) as previously described ( Wang Q. et al, 2020 ; Li et al, 2021 ). Picrosirius red staining was performed with paraffin-embedded liver sections using a commercially available kit (Sigma Aldrich) as previously described ( Li et al, 2021 ). For hydroxylproline quantification, ∼10 mg of liver tissue was weighed, homogenized, and hydrolyzed in HCl (10N) at 120°C for 3 h. Supernatants were transferred to a 96-well plate and hydroxylproline content was determined by colorimetry (Sigma Aldrich, MAK008).…”
Section: Methodsmentioning
confidence: 99%
“…Histological analyses were performed essentially as described before (Li et al, 2021). Paraffin sections were stained with were blocked with 10% normal goat serum for 1 h at room temperature and then incubated with anti-MYCN (Proteinch, 1:200) or anti-PCNA (Abcam, 1:200) antibodies.…”
Section: Histologymentioning
confidence: 99%